2010
DOI: 10.1016/j.conbuildmat.2010.04.045
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the effects of rice husk ash particle size on strength, water permeability and workability of binary blended concrete

Abstract: This study develops the compressive strength, water permeability and workability of concrete by partial replacement of cement with agro-waste rice husk ash. Two types of rice husk ash with average particle size of 5 micron (ultra fine particles) and 95 micron and with four different contents of 5%, 10%, 15% and 20% by weight were used. Replacement of cement up to maximum of 15% and 20% respectively by 95 and 5 μm rice husk ash, produces concrete with improved strength. However, the ultimate strength of concret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(121 citation statements)
references
References 22 publications
6
109
3
3
Order By: Relevance
“…Fine particles are capable to fill the vacancies and produce more densified specimens. This has been confirmed in some works done on concrete specimens 20 , but as authors' knowledge there is not any reports confirm this matter in geopolymers.…”
Section: Total Specific Pore Volumesupporting
confidence: 54%
“…Fine particles are capable to fill the vacancies and produce more densified specimens. This has been confirmed in some works done on concrete specimens 20 , but as authors' knowledge there is not any reports confirm this matter in geopolymers.…”
Section: Total Specific Pore Volumesupporting
confidence: 54%
“…Later, Jones et al (2006) found that the addition of ultrafine fly ash would also increase the flow of mortar. On the use of rice husk ash, Cordeiro et al (2009) found that the addition of ultrafine rice husk ash would reduce the yield stress and viscosity only when the HRWRA dosage is increased to allow for the increase in solid surface area whereas Givi et al (2010) showed that partial replacement of cement by a coarser rice husk ash gives better workability than by a finer rice husk ash. On the use of cement with different fineness, Kaufmann et al (2004) found that the rheological properties of cement paste could be improved by blending normal cement with ultrafine cement.…”
Section: Introductionmentioning
confidence: 99%
“…It also caused a reduction of chloride penetration and permeability. Alireza Naji Givi, et al [9] demonstrated that the addition of ultra fine RHA with average particle size of 5 microns provided better mechanical and durability properties of concrete. The partial replacement of RHA at 10% exhibited higher compressive properties and also showed an appreciable reduction in water permeability of hardened concrete.…”
Section: S In Rice Husk Ashmentioning
confidence: 99%